Economic Development of Myanmar - Myat Thein (Book collections on Project MUSE., 2004)
There are a number of excellent studies by eminent Myanmar economists as well as scholars from abroad covering different post-war periods and/or various aspects of development in Myanmar. What this book does is to bring them altogether, as it were, under one roof by recasting bits and pieces of their work according to the author's own understanding. In doing so, a holistic approach was adopted in order to have a well-rounded account of developments over the past fifty years or more. In addition, an attempt has also been made to present the major developments at different periods of time between 1948 and 2000 in a simple, but not over simplified, reader-friendly format so as to reach as wide an audience as possible. It is the author's ardent wish that not only students and policy-makers, but Myanmar people in all walks of life will read the book, discuss it, and work together for a better future.